Cutaneous leishmaniasis: an underdiagnosed entity in the first contact - Sierra Franco , Andrea; Talamante Madrid, María Jimena; Espejo Nuño, Reneta Montserrat; Davila Baeza, Daniela Alejandra; Espinoza Hernández, Martha Yanelly; Cano Muñoz, Edit; Medrano, María Erika Boza (International Journal of Research in Dermatology, 2023)
Leishmaniasis is a chronic, vector-borne parasitic disease caused by a flagellated protozoan of the genus Leishmania, which has more than 20 species. Usually, it is a disease that affects the tropical and subtropical populations of the world. The disease is transmitted through the bite of female mosquitoes of the genus Lutzomyiaen and Phlebotomusen. The clinical presentation and its manifestations are variable, they are affected by the species and immunological state of the host. Generally, three main types are distinguished: the most frequent presentation and with the best prognosis is cutaneous leishmaniasis (CL), the second is known as mucocutaneous leishmaniasis (MCL), and the third presentation is visceral leishmaniasis, which puts endanger the life of the person presenting it. Leishmaniasis is related to various risk factors, including: poverty, malnutrition, migration, and inadequate housing conditions; in addition, people who work in rural areas, such as farmers, farmers, or the military in endemic areas, are at greater risk of suffering a bite by a transmitting mosquito. Due to its variable manifestations and greater affectation in poor areas, it is a pathology that is normally overlooked. The objective of this review is to define and differentiate the most frequent types of presentation as well as their cutaneous manifestations, and to provide extensive information on diagnostic methods. Briefly, general information on the pathology and treatment of these lesions will be provided.